Hear our voice: Local perceptions are critical to understand deforestation dynamics in post-conflict zones - Sanchez, Angie L.; Gutierrez, Diana (2025)
In Colombia’s post-conflict regions, deforestation is more than an environmental issue—it reflects deep social transformations. A new study reveals how local perceptions can unlock better forest conservation strategies rooted in community realities.